PENGARUH ELECTRONIC WORD OF MOUTH DAN BRAND IMAGE TERHADAP PURCHASE INTENTION PADA PT ALPHA REAL ESTATE DI KOTA BATAM - Lee, Dick; Saputra, Asron (SCIENTIA JOURNAL, 2019)
Along with the evolution of the internet, electronic word of mouth and brand image has become an important phenomenon to increase purchase intention. The purpose of the study is to determine and analyzing the influence of electronic word of mouth and brand image on purchase intention of PT Alpha Real Estate in Batam City. The data used is primary is by distributing questionnaires. The sample used were 152 respondents distributed to customers. Using purposive sampling method, multiple linear regression analysis, t test to determine the effect partially, F test to analyze the effect simultaneously and test coefficient of determination R to find out how strong the level of influence of the independent variables on the dependent variable and by using data collection techniques that are saturated samples or census techniques. In addition, the researcher also tested the validity and reliability of the instrument with the help of SPSS version 21 program. The results show that electronic word of mouth has a positive effect partially on purchase intention. Brand image has a positive effect partially on purchase intention. Electronic word of mouth and brand image have positive significant effect simultaneously on purchase intention. 2